Plant nutrition basics - Jones, J. Benton (Anderson, S.C.: On Sat One Television Productions, 1994)
How plants grow? How do plants obtain those elements essential for normal growth and development? What are the essential elements? The questions are answered in this video.
Keywords: Plants -- Nutrition